Subsurface structural mapping from high-resolution gravity data using advanced processing methods - Luan Thanh Pham; Duong Anh Nguyen; Ahmed M. Eldosouky; Kamal Abdelrahman; Tich Van Vu; Naif Al-Otaibi; Elkhedr Ibrahim; Sherif Kharbish (Journal of King Saud University: Science, 2021)
The study area has a complex geological structure and is studied for mapping the density interfaces using geophysical techniques. However, it has not been studied for mapping geological structures, such as contacts and faults that appear as lineaments in gravity data. In this study, the lineaments in the area have been delineated using Bouguer gravity anomaly data, though some modern processing methods, such as horizontal gradient amplitude (HGA), tilt angle of horizontal gradient amplitude (THGA), and enhancement of horizontal gradient amplitude (EHGA). Most of the identified lineaments are trending in the NW–SE direction and some WE-trending lineaments in the southeastern region. This study provides new information for a better understanding of the structural framework and tectonic setting of the Thua Thien Hue area.